Prognostic significance of PD‐L1 expression on cell‐surface vimentin‐positive circulating tumor cells in gastric cancer patients. Issue 4 (28th February 2020) - Liu, Mengyuan; Wang, Ruoyu; Sun, Xuren; Liu, Yuting; Wang, Zhi; Yan, Jin; Kong, Xiangyu; Liang, Shanshan; Liu, Qiuge; Zhao, Tong; Ji, Xuening; Wang, Gang; et al.
Abstract : Although circulating tumor cells (CTCs) have shown promise as potential biomarkers for diagnostic and prognostic assessment in gastric cancer (GC), determining the predictive and prognostic value of programmed death‐ligand 1 (PD‐L1)‐positive CTCs in patients with GC is a challenge. Here, we identified that the expression of total vimentin (VIM) protein was positively correlated with PD‐L1 and inhibited CD8 + T‐cell activation in patients with GC according to bioinformatics analysis. Notably, coexpression of PD‐L1 and cell‐surface VIM (CSV) was detected by immunofluorescence and immunohistochemistry assay in locally advanced GC tumor specimens and metastatic lymph nodes. Likewise, CSV expression level was significantly decreased after transiently knocking down PD‐L1 in GC cell lines. Based on our established CTC detection platform, CTCs were isolated from peripheral blood samples collected from 70 patients (38 resectable and 32 unresectable) with GC using magnetic positive selection and a CSV‐specific monoclonal antibody, 84‐1. CSV + PD‐L1 + CTCs were observed in 50 of 70 (71%) GC patient samples, ranging from 0 to 261 mL −1 . A higher number of CSV + PD‐L1 + CTCs were significantly associated with a short survival duration and poor therapeutic response. This study demonstrated that detection of PD‐L1 + CTCs using a CSV‐enrichment method has promising value as a clinically relevant prognostic marker for GC. Abstract : CSV + PD‐L1 + CTC exhibits epithelial mesenchymal transition subtype, which can be observed in GC patient's peripheral blood samples. A higher number of CSV + PD‐L1 + CTCs are significantly associated with a short survival duration and poor therapeutic response.